Effectiveness of Limited Training with Cone Obstacle and Jump on Smash Volleyball Ability - Amansyah, Amansyah -; Asmawi, Asmawi; Samsudin, Samsudin (Department of Physical Education, Sport, Health and Recreation, 2022)
The purpose of this research was to determine the effectiveness of the training using cone obstacle by jumping to improve the volleyball smash ability in athletes trained in the student activity unit of a public university in Medan. This study employed an experimental design with a one-group pretest-posttest design. The study was conducted at Student Activity Units at State Universities in Medan. The participants were 32 (F= 16 and M= 16) athletes who were being coached in the Volleyball Student Activity Unit. Collecting data used observations, interviews, and tests. Technique data analysis used Paired Sample t-test. The results showed that the exercise model using a cone hurdle with jumping had improved the athletes' volleyball smash skills even though the COVID-19 pandemic had not improved. The concept of a dissertation exercise with strict procedures for health protocols is the right solution so that athletes still have quality volleyball skills. The results of the study also have implications for understanding volleyball exercises during the COVID-19 pandemic, which limits activity.